2005
DOI: 10.2337/diacare.28.9.2217
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Coronary Angiographic Studies of Patients With Angina Pectoris and Impaired Glucose Tolerance

Abstract: OBJECTIVE -We investigated the morphological characteristics of coronary arteries in patients with impaired glucose tolerance (IGT) using computer-assisted quantitative coronary angiography. IGT is an independent risk factor for cardiovascular disease. However, the morphological changes developing in the coronary arteries of patients with IGT remain unknown.RESEARCH DESIGN AND METHODS -A total of 534 patients with angina pectoris were studied. Of these, 144 patients were being treated for diabetes. The remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…Other imaging studies have also identified the presence of inflamed and extensive disease substrates in patients with impaired glucose tolerance (IGT) [10][11][12] . These observations indicate that earlystage diabetic patients constitute an important therapeutic target for the prevention of future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Other imaging studies have also identified the presence of inflamed and extensive disease substrates in patients with impaired glucose tolerance (IGT) [10][11][12] . These observations indicate that earlystage diabetic patients constitute an important therapeutic target for the prevention of future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, QCA is more accurate, objective and reproducible than manual caliper measurements. 19,23,24 The parameters we used (ie, AVD and ALL) enabled us to evaluate in detail the absolute values for the entire coronary tree, and our QCA analysis revealed that severe atherosclerotic changes had developed in women ≥75 years old (Figures 2,4). In addition, the morphological characteristics of CAD were more severe in the SES era than in the BMS era, because the ALL was >30 mm on average.…”
Section: Morphological Characteristics Of Cad In Elderly Womenmentioning
confidence: 99%
“…4.0, Medis, Leiden, The Netherlands), as reported previously. 19 Briefly, we measured the diameter of the middle section in each major coronary segment (segments 1-3 of the right coronary artery, segments 6-8 of the left anterior descending artery, and segments 11 and 13 of the left circumflex artery) in order to calculate the average vessel diameter (AVD) for each patient. We defined segments with an irregular edge that narrowed to a diameter ≤1.5 mm as diseased lesions and calculated the average lesion length (ALL).…”
Section: Coronary Angiography and Quantitative Analysismentioning
confidence: 99%
“…Several previous studies demonstrated that diabetic patients have more diffuse and longer small vessel and multivessel coronary lesions. 3,4 For these patients, judgment as to whether or not revascularization should be performed is not easy due to complicated lesion morphology. We suggest that physiological evaluation methods should be performed, particularly in patients with diabetes.…”
mentioning
confidence: 99%